1995
DOI: 10.1016/0014-5793(95)01207-u
|View full text |Cite
|
Sign up to set email alerts
|

The peripheral cannabinoid receptor: adenylate cyclase inhibition and G protein coupling

Abstract: Two cannabinoid receptors, designated neuronal (or CB1) and peripheral (or CB2), have recently been cloned. Activation of CB1 receptors leads to inhibition of adenylate cyclase and N-type voltage-dependent Ca 2+ channels. Here we show, using a CB2 transfected Chinese hamster ovary cell line, that this receptor binds a variety of tricyclic cannabinoid ligands as well as the endogenous ligand anandamide. Activation of the CB2 receptor by various tricydic cannabinoids inhibits adenylate cyclase activity and this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
1
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(123 citation statements)
references
References 17 publications
7
112
1
3
Order By: Relevance
“…We demonstrated that anandamide has both antihyperalgesic and anti-edemic effects. Most studies have found that anandamide does not activate the CB 2 receptor (Facci et al, 1995;Bayewitch et al, 1995) except at very high concentrations (greater than 75 mM; Lee et al, 1995) supporting the hypothesis that anandamide's effects in the present study are mediated by the CB 1 receptor. Moreover, anandamideinduced antihyperalgesia was inhibited by the coadministration of the selective CB 1 receptor antagonist SR 141716A.…”
Section: Discussionsupporting
confidence: 84%
“…We demonstrated that anandamide has both antihyperalgesic and anti-edemic effects. Most studies have found that anandamide does not activate the CB 2 receptor (Facci et al, 1995;Bayewitch et al, 1995) except at very high concentrations (greater than 75 mM; Lee et al, 1995) supporting the hypothesis that anandamide's effects in the present study are mediated by the CB 1 receptor. Moreover, anandamideinduced antihyperalgesia was inhibited by the coadministration of the selective CB 1 receptor antagonist SR 141716A.…”
Section: Discussionsupporting
confidence: 84%
“…Administration of SR144528 alone had no effect on microglial proliferation. Because the CB 2 receptor is a G-protein coupled receptor (GPCR) whose effects are known to be mediated through the G␣ i subunit (Bayewitch et al, 1995), we sought to demonstrate an inhibition of CB 2 receptor-mediated proliferation by concurrently treating cells with 100 ng/ml pertussis toxin, an irreversible G␣ i /G␣ o inhibitor. However, normal M-CSF-dependent proliferation (i.e., in the absence of cannabinoids) was inhibited by pertussis toxin (33% of untreated control, data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…For example, high concentrations of CB agonists inhibit inositol trisphosphate formation (Nah et al, 1993), and elicit the release of intracellular calcium (Felder et al, 1992; as well as the liberation of arachidonic acid (Howlett, 1995). One proposed explanation for these receptor-independent eects is that the cannabinoids incorporate into the membrane and directly modulate the activity of integrated membrane proteins such as Ga i (Bayewitch et al, 1995). Independently of whether or not the eects of D…”
Section: Discussionmentioning
confidence: 99%